Experiences of patients undergoing chemotherapy - a qualitative study of adults attending Uganda Cancer Institute - Wampaalu, Peter B.; Eriksson, Lars E.; Naamala, Allen; Nabirye, Rose C.; Wettergren, Lena (African health sciences, 2016)
Background: Cancer is a global public health challenge and how patients in countries with poor healthcare infrastructure experience cancer treatment is largely unknown. Purpose: The objective of this study was to describe adult Ugandan cancer patients’ experiences of undergoing chemotherapy treatment. Methodology: Using a qualitative descriptive design, seven in-patients with varying cancer diagnoses at the Uganda Cancer Institute were interviewed about their experiences of undergoing chemotherapy treatment; the interviews were transcribed and analysed thematically. Results: The analysis resulted in nine subthemes, which were categorized under three main themes: ‘experiences related to the body’, with the subthemes dry and sensitive skin, changes in eating and bowel habits, fever and feelings of abnormal body sensation; ‘thoughts and feelings’, with four subthemes reflecting the psychosocial impact of chemotherapy; and ‘actively dealing with discomfort’, with three subthemes describing how patients dealt with side effects, such as by sticking to a diet. Conclusion: Receiving chemotherapy treatment is difficult, and the side effects negatively influenced patients’ bodies and moods. Dealing actively with discomfort and accepting negative impacts in hope of a cure helped the participants manage the acute complications related to the treatment. We recommend the development of interventions to ease discomfort due to chemotherapy.
Keywords: Cancer; chemotherapy; experiences; nursing; qualitative